Analisis Kinerja Keuangan Anggaran Pendapatan dan Belanja Daerah Kota Medan - Lubis, Putri Kemala Dewi; Handayani, Lily; Hidayah, Nurika Fahqna (Asosiasi Dosen Akuntansi Indonesia, 2023)
This study aims to evaluate the performance of the Medan city budget for the 2016-2020 period in terms of spending variance, shopping growth, shopping harmony, shopping efficiency and regional spending to GRDP. This research uses descriptive research with a case study approach because this research seeks to reveal cases, describe and then interpret them by utilizing data based on numbers. The results showed that the budget performance of the Medan City government was generally said to be good. This can be seen from (a) Shopping Variance with an average of 78%, (b) Shopping Growth with an average of 2%, (c) Expenditure Per function realized 92.69%, Operating Expenditure with an average of 39%, Capital Expenditure with an average of 27%, Direct Expenditure with an average of 81% and Indirect Expenditure with an average of 49%, Regional Expenditure Efficiency showing an average of below 100% which is 78%, and Expenditure on GRDP with an average of 3%.